2021
DOI: 10.1038/s41598-021-90970-5
|View full text |Cite
|
Sign up to set email alerts
|

The threshold effect of factors associated with spontaneous abortion in human-assisted reproductive technology

Abstract: We explored the independent risk factors associated with cases of spontaneous abortion in infertile patients treated with human-assisted reproductive technology (ART) and established a smooth curve fit and perform a threshold effect analysis can provide guidance and a valuable reference for predicting the probability of spontaneous abortion. This was a retrospective cohort study of 16,097 patients successfully conceived with ART in Shangqiu First People's Hospital from June 2013 to December 2018. Overall, 2,37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Feodor et al ( 18 ) found that the risk of spontaneous abortion in pregnant women was significantly higher when maternal age was over 40 years old. Two small-sample studies in China found that pregnant women who were 32 years old or older showed a stronger risk association with spontaneous abortion ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feodor et al ( 18 ) found that the risk of spontaneous abortion in pregnant women was significantly higher when maternal age was over 40 years old. Two small-sample studies in China found that pregnant women who were 32 years old or older showed a stronger risk association with spontaneous abortion ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies categorized participants as either above or below 30 or 35 years old, which limited the comparability between scientific and clinical guidance given by different studies. Most domestic studies concentrated on establishing a linear relationship between maternal age and risk of spontaneous abortion or recurrent miscarriage, and only two small-sample studies discussed a non-linear relationship between maternal age and risk of spontaneous abortion, finding that the risk is slightly elevated in the youngest mothers and then rose sharply in mothers 32 years and older ( 20 , 21 ). The precise form of the non-linear relationship between maternal age and spontaneous abortion risk is unclear, nor is there any discussion of a threshold effect of that.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spontaneous abortion rate increases 35 . Chen, L., et al have proven that the development days and quality of biopsied blastocysts affect the abortion rate 37 . High-quality blastocysts are associated with a higher implantation rate and live rate.…”
Section: Discussionmentioning
confidence: 99%
“…With age, the number and quality of oocytes significantly decreases, the number of mitochondria decreases, there is a significant decrease in the content of ATP in the cytoplasm, and the proportion of abnormal embryonic chromosomal structures increases. Spontaneous abortion is closely related to chromosomal abnormalities of the embryo18,19, several studies have shown that chromosomal abnormalities are the most common cause of spontaneous abortion so it can be concluded that the older a woman is, the higher the chances of having a spontaneous abortion (Li, Niu, Feng, Yan, & Chen, 2021). At the beginning of the abortion, bleeding occurs in the decidua basalis followed by necrosis of the surrounding tissue, this causes the products of conception to be partially detached, so that the uterus considers the products of conception to be foreign bodies that must be removed so that the uterus contracts.…”
Section: Discussionmentioning
confidence: 99%